The MicroRNA828/MYB12 Module Mediates Bicolor Pattern Development in Asiatic Hybrid Lily (Lilium spp.) Flowers - Yamagishi, Masumi; Sakai, Moeko (Frontiers in Plant Science, 2020)
Some Asiatic hybrid lily cultivars develop bicolor tepals, which consist of anthocyanin-pigmented upper halves and un-pigmented lower halves. MYB12, a subgroup 6 member of R2R3-MYB that positively regulates anthocyanin biosynthesis, is down-regulated in the lower halves. However, MYB12 is usually expressed over entire tepal regions in numerous lily cultivars. Why MYB12 of bicolor cultivars exhibits variable expression spatially in a single tepal remains unclear. Since the lily MYB12 mRNA harbored a binding site for microRNA828 (miR828), the involvement of miR828 in variable spatial accumulation of MYB12 transcripts was evaluated. We analyzed the cleavage of MYB12 mRNA, mature miR828 accumulation, and MYB12 transcript-derived siRNA generation (microRNA-seq). In the bicolor tepals, mature miR828 was more highly accumulated in the lower halves than in the upper halves, and miR828-directed cleavage of MYB12 transcripts was observed predominantly in the lower halves. Moreover, the cleavage triggered the production of secondary siRNA from MYB12 transcripts, and the siRNAs were accumulated predominantly in the lower helves. Consequently, miR828 suppressed MYB12 transcript accumulation in the white region, and the miR828/MYB12 module participated in the development of bicolor patterns in lily flowers. The results present the first example of a microRNA mediating flower color patterns. Finally, we discuss the potential of miR828 creating flower color variations through suppressing the activity of subgroup 6 R2R3-MYB positive regulators in other species.